Timing Science: The Temporal Role of Scientists in the Construction of Data - Caitlin Donahue Wylie (Philosophy, Theory, and Practice in Biology, 2024)
The processes of producing scientific knowledge rely on the temporality of data, yet they also obscure this relationship. Scientists hope that knowledge claims can stand relatively independent from their context of production. Instead, a more realistic and trustworthy view would be to embrace data’s history and “journey” (Leonelli and Tempini 2020) as a component of the knowledge claims that these data inspire. These journeys describe how data and people interact and thereby influence each other’s identity and epistemic worth. In this paper, I propose a model to help philosophers and other analysts pay closer attention to the people who work with scientific data, specifically by considering how these practitioners conceptualize time. I argue that how practitioners experience time reflects the personal, professional, epistemic, and ethical values that guide their decisions about how to do science. These conceptions of time differ by profession, career stage, identity, institutional context, and other factors specific to practitioners’ lives as well as their scientific or disciplinary culture. I draw from two case studies of vertebrate fossils to illustrate how various conceptions of time co-exist for practitioners, as indicators of the values that guide practitioners’ decisions as they do scientific work.